Kajian Rencana Pengelolaan dan Pemantauan Lingkungan Hidup Gedung Balai Pendidikan “X” DIY - Mohamad Sholikin; Muhammad Abdus Salam Jawwad; Slamet Sujarwa (Yayasan Literasi Sains Indonesia, 2023)
Progressive development in D.I. Yogyakarta has an impact on environmental problems. This indicates that some of the past developments still do not meet environmental sustainability aspects. Through government regulations related to businesses and/or activities that do not yet have environmental documents but have business licenses and have been operating, they are required to make DELH/DPLH as an instrument for environmental management and monitoring. The purpose of this study are: (1) to identify the activities that have been running in the Education Building “X” in DIY, (2) to identify the potential impact on the environment as a result of the Education Building “X” in DIY operation. The method used in this study is a descriptive approach method. The Environmental Management and Monitoring Plan for the Education Building “X” in DIY were prepared to complement the Environmental Evaluation Document (DELH) which is guided by the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. P.102/2016 concerning Guidelines for Preparing Environmental Documents for Businesses and /or Activities That Have Business and/or Activity Permits but Do Not Have Environmental Documents. This study is a source of information on geophysical-chemical, social, cultural, and economic problems that may arise in the future and methods of prevention and management as a result of these operational activities.